Multiwavelength observations of the transitional millisecond pulsar binary XSS J12270−4859. Issue 2 (9th October 2015) - de Martino, D.; Papitto, A.; Belloni, T.; Burgay, M.; De Ona Wilhelmi, E.; Li, J.; Pellizzoni, A.; Possenti, A.; Rea, N.; Torres, D. F.
Abstract : We present an analysis of X-ray, ultraviolet and optical/near-IR photometric data of the transitional millisecond pulsar binary XSS J12270−4859, obtained at different epochs after the transition to a rotation-powered radio pulsar state. The observations, while confirming the large-amplitude orbital modulation found in previous studies after the state change, also reveal an energy dependence of the amplitudes as well as variations on time-scale of months. The amplitude variations are anticorrelated in the X-ray and the UV/optical bands. The average X-ray spectrum is described by a power law with Γ index of 1.07(8) without requiring an additional thermal component. The power-law index Γ varies from ∼1.2 to ∼1.0 between superior and inferior conjunction of the neutron star. We interpret the observed X-ray behaviour in terms of synchrotron radiation emitted in an extended intrabinary shock, located between the pulsar and the donor star, which is eclipsed due to the companion orbital motion. The G5-type donor dominates the UV/optical and near-IR emission and is similarly found to be heated up to ∼6500 K as in the disc state. The analysis of optical light curves gives a binary inclination 46° ≲ i ≲ 65° and a mass ratio 0.11 ≲ q ≲ 0.26. The donor mass is found to be 0.15 ≲ M 2 ≲ 0.36 M⊙ for a neutron star mass of 1.4 M⊙ . The variations in the amplitude of the orbital modulation are interpreted in terms of small changes in the mass-flow rate from the donor star. The spectral energy distribution from radio to gamma-rays is composed by multiple contributions that are different from those observed during the accretion-powered state.